Examining the Determinant of Purchase Intention and Purchase Decision for Green Product: SEM Analysis - Mutmainah, Isbandriyati; Eha Hasni Wahidhani (Apollo: Journal of Tourism and Business, 2024)
A climate change and global warming have an impact on increasing public awareness of environmental problems. Consumers are becoming more aware that their consumption habits have a direct impact on the environment and are taking on greater responsibility for environmental sustainability. Based on this phenomenon, this study’s purpose is to explore the influence of green marketing strategy, green product knowledge, green purchasing behavior toward purchasing intention and decision for green products, among non-member Tupperware consumers. The Structural Equation Modeling analysis method was used for 225 selected respondents were collected through quota sampling and accidental sampling, and submitted online using the google form which were submitted via social media and Whatsapp groups. The finding showed that green purchasing intention directly affects purchasing decision. Green marketing strategies, product knowledge and green purchasing behavior indirectly affects green purchasing decision through mediation of green purchasing intention, with green marketing strategies providing the greatest influence. These results provide information to management with insights into the contribution of green marketing strategy, consumer knowledge of green products, and consumer purchasing behavior in increasing the intention and the decision to buy green products, and encourages stakeholders to improve the green marketing strategy through pro-environment product innovation and promotion to increase the consumers’ intent for buy green product